Crescimento inicial de cana-de-açúcar em latossolo com gradiente de saturação por alumínio e submetido à aplicação de vinhaça - Viglio, Larissa Marques (2014)
An important strategy to round the problem of high acidity in soil and the toxicity aluminum (Al)consequent, limiting the full sugarcane development, it is based on the use of suitable varieties to these conditions. The application of vinasse is one practical routine in sugarcane cropping. The vinasse effect as fertilizer is well known, principally by reducing the use of potassium fertilizers. However, vinasse may attenuate the toxic effects of Al in soil by formation of complexes with organic acids of low molecular weight, improving further deepening of the root system sugarcane. The aim of this work was to study tolerance of three sugarcane varieties (RB855453, RB966928 e RB867515) to Al toxicity and to assess the influence of vinasse in the expansion of the root system in dystrophic Red Yellow Oxisol with gradient of Al saturation. The experiment was carried out in the greenhouse, on an entirely randomized design, in factorial arrangement, with three replicates. Sugarcane seedling were transplanted to PVC columns (0,8 m), each column consisted of four PVC rings. The PVC rings were filled with soil samples that offered an ascending gradient of Al saturation in depth (m%= 0,7; 7,9; 40,8; 62,6). The collection of the experiment was conducted 120 days after planting and it was determined the leaf chlorophyll index (ICF), stem diameter, plant height, dry weight of shoot and stratified root system dry matter . The largest amount of total root system dry matter in soil without the supply of vinasse was obtained from the RB867515 but with vinasse application this characteristic was presented by RB867515 and RB855453. The RB867515 was considered the most tolerant to Al, however the sugarcane varieties classification order based on tolerance index has varied according to vinasse application. The shoot biometric parameters, excepted by the stem diameter, were not considered indicators to differentiate the sugarcane genotypes from the phytotoxic Al in soil, as well as the ICF could not be adopted as an indicative parameter due by this stress. There were no significant alterations in soil chemical properties, especially in reducing the levels of Al and Al saturation index 90 days after vinasse application. The vinasse effect in increasing the percentage of roots at depth of 40 to 80 cm, has been verified only by RB966928.